2014
DOI: 10.4073/csr.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

School‐Based Interventions to Reduce Dating and Sexual Violence: A Systematic Review

Abstract: This Campbell systematic review examines the effectiveness of school‐based interventions to reduce or prevent violence in intimate relationships. The review focused on programmes to change attitudes and beliefs, reduce perpetration and victimization, and change behaviours. The systematic review included 23 studies. Prevention programmes improve young people's knowledge about, and attitudes towards, dating violence. These effects were sustained at follow up. Students in the intervention group showed moderate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 115 publications
5
86
0
Order By: Relevance
“…Much research has focused on individual-level risk factors for ARA victimization and perpetration (e.g., Foshee et al 2011;Garthe et al 2016;Vagi et al 2013), but prevention efforts to address these risks have had varying results. For instance, evaluations of a few middle and high school based prevention programs show limited impact (De La Rue et al 2014). Overall, programmatic efforts tend to focus on adolescent attitudes, intentions, and skills, rather than community norms and structural factors, consistent with the research focus to date.…”
Section: Introductionmentioning
confidence: 80%
“…Much research has focused on individual-level risk factors for ARA victimization and perpetration (e.g., Foshee et al 2011;Garthe et al 2016;Vagi et al 2013), but prevention efforts to address these risks have had varying results. For instance, evaluations of a few middle and high school based prevention programs show limited impact (De La Rue et al 2014). Overall, programmatic efforts tend to focus on adolescent attitudes, intentions, and skills, rather than community norms and structural factors, consistent with the research focus to date.…”
Section: Introductionmentioning
confidence: 80%
“…Some programs have shown promise and, traditionally, schools have been the primary setting for dating violence prevention programs (De La Rue, Polanin, Espelage, & Pigott, 2014). Some newer programs such as Families for Safe Dates have also engaged parents (Foshee, Reyes, Ennett, et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To date, evidence-based programs have mainly been carried out in the United States and Canada; and they are still scarce across Europe and South America [ 13 ]. Meta-analyses and systematic reviews conducted thus far [ 14 , 15 , 13 ] coincide in terms of heterogeneity across different programs, their moderate methodological quality, and their efficacy in bringing about changes in knowledge and beliefs associated with love and violence reaching effect sizes of .47 [ 14 ]. However, data on their efficacy in reducing dating aggression and/or victimization have proved less conclusive; only three randomized controlled trials (RCTs) have been found to yield positive outcomes in this area, namely Safe Dates [ 16 ], The Fourth R [ 17 ], and S tepping Stones [ 18 ] although, the effect sizes of these interventions were from moderate to low.…”
Section: Introductionmentioning
confidence: 99%